Technologies for providing of forensic investigation of computer and technology crimes - V. V. Malikov; I. V. Benediktovich; S. A. Churukanov (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki)
Technologies for providing of forensic investigation of computer and technical crimes involving legal, organizational and technical components which provide detection, investigation and prevention of such crimes are proposed.